2016
DOI: 10.1039/c5fo00904a
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of intestinal tissues from mice fed with Lentinula edodes-derived polysaccharides

Abstract: Lentinula edodes-derived polysaccharides are well known for their immunomodulation and antitumor activities. However, the mechanisms of action have not been fully elucidated. This study presents proteomic analysis of the colon and small intestine from mice fed with an immunostimulating heteropolysaccharide L2 from the fruit body of L. edodes. Two-dimensional gel electrophoresis (2-DE) and MALDI-TOF-TOF MS/MS were employed to characterize the protein profiles. Twenty nine gel spots representing 20 proteins in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…Hsp70 has been reported to exhibit adjuvant activity by promoting adaptive immune response to antigenic cells [21]. Xu et al’s proteomic study showed that Hsp70 and Hsp 90-beta were up-regulated and down-regulated, respectively, in intestinal tissues harvested from mice fed with Lentinula edodes -derived polysaccharides compared to the control group that received a normal diet [22]. Interestingly, the authors also observed a lower level of Annexin A2 in the polysaccharide group, which mirrored the finding in our current study.…”
Section: Resultsmentioning
confidence: 99%
“…Hsp70 has been reported to exhibit adjuvant activity by promoting adaptive immune response to antigenic cells [21]. Xu et al’s proteomic study showed that Hsp70 and Hsp 90-beta were up-regulated and down-regulated, respectively, in intestinal tissues harvested from mice fed with Lentinula edodes -derived polysaccharides compared to the control group that received a normal diet [22]. Interestingly, the authors also observed a lower level of Annexin A2 in the polysaccharide group, which mirrored the finding in our current study.…”
Section: Resultsmentioning
confidence: 99%
“…Three jejunum tissue samples were randomly selected from each O group and OL2 group. Protein extraction was conducted according to the previous method with slight modifications [21,23]. In brief, about 100 mg tissue samples were ground rapidly into powders in liquid nitrogen in a mortar.…”
Section: Itraq-based Proteomics Analysis 241 Protein Extractionmentioning
confidence: 99%
“…In our previous study, a heteropolysaccharide consisting of glucose, galactose, and arabinose with an average molecular weight of 26 kDa, named L2, extracted from the fruit body of Lentinula edodes [18], exhibited immunoenhancing actions and altered the microbial community along the intestinal tract in adult mice [19,20]. Two-dimensional gel electrophoresis (2-DE) combined with mass spectrometry (MS)-based proteomic study and real time (RT)-PCR analysis revealed that metabolism, binding, structural components, and response to stimulus might participate in L2-induced regulatory mechanisms [20,21]. Moreover, L2 induced greater impacts on the small intestinal region than on the colon regarding protein and gene expression levels in adult mice [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that one type of L. edodes ‐derived polysaccharide, named L2, showed immune‐stimulating activity in vitro and enhanced immune responses in vivo characterized by alterations in the gut microbiota and differential expressions in genes and proteins in the gut of adult mice (Xu, Yan, & Zhang, ; Xu, Yang, Ning, & Zhang, ; Xu & Zhang, ). L2 also exhibited anti‐ageing effects by partially restoring age‐attenuated immune functions and reversing the age‐altered gut microbial communities (Xu, Yang, Ning, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%